Systematic bioinformatics analysis reveals the role of shikonin in blocking colon cancer progression by identifying senescence-induced genes - Wenna Liu; Yujia Zhao; Qingqing Liu; Dan Wu; Wenxuan Li; Zhenkai Fu; Le Yang; Ying Liang (Frontiers Media S.A., 2024)
Shikonin, a naturally occurring naphthoquinone compound extracted from comfrey plants, has antitumor, anti-inflammatory, and antimicrobial properties. Cell senescence plays a key role in preventing tumor progression. It is unclear whether shikonin has an effect on cell senescence in colon cancer. In the current study, we first determine the IC50 values of shikonin on colon cancer cell lines HT29 and HCT116. Then, we verified the inhibitory effects of shikonin on the proliferation and migration abilities of colon cancer cell lines HT29 and HCT116 using cell counting kit-8, colony formation, and wound healing assays. Next, we identified a series of potential targets using high-throughput mRNA sequencing and identified 210 upregulated and 296 downregulated genes. KEGG profiling revealed eight downregulated genes associated with cell senescence: CCNB3, IL-1α, CXCL8, CDKN2A, MYC, IGFBP3, SQSTM1, and GADD45G. Among them, CXCL8 and CDKN2A were associated with poor prognosis in patients with colon cancer, suggesting that their downregulation by shikonin could improve patient survival. Furthermore, SA-β-galactosidase staining revealed that the percentage of cellular senescence in colon cancer cells was significantly increased after shikonin treatment. Molecular docking revealed that shikonin suppressed colon cancer progression by blocking CXCL8 activity. Based on these findings, we deem that shikonin might induce senescence and exert antitumor activity in colon cancer cells by downregulating CDKN2A and CXCL8. This provides a new molecular mechanism and potential therapeutic target for shikonin to inhibit colon cancer progression.